O50 New guidelines to reduce unnecessary blood tests, delayed discharge and costs following robot assisted radical prostatectomy. (30th July 2021) - Fricker, M; Nathan, A; Hannah, N; Rashid, A; Patel, S; Phuah, Y; Flora, K; Cleaveland, P; Kasivisvanathan, V; Williams, N; Miah, S; Shah, N; et al.
Abstract: Introduction: Routine postoperative blood tests (POBT) are used to evaluate the impact of surgery on pre-existing co-morbidities and to detect early complications. This practice dates back to an era of open surgery, when blood loss and complication rates were higher. We propose new guidelines to improve the specificity of POBT. Method: The cases of 1040 consecutive patients who underwent a primary or salvage RARP at two large tertiary urology centres in the United Kingdom were retrospectively reviewed, and new guidelines were designed. The guidelines were prospectively validated in a cohort of 300 patients. Result: Derivation Dataset 3% and 5% had intra- and post-operative Clavien-Dindo complications, respectively. 15% had clinical concerns postoperatively. 0.9% required perioperative transfusion. 78% had routine blood tests without clinical concerns, none of whom developed a complication. 98% of complications were suspected by clinical judgement. 6% of patients had a discharge delay of ≥ 1 days due to delayed or incomplete blood tests. Validation Dataset No significant difference existed in complication, clinical concern or transfusion rates between the derivation and validation datasets. New guidelines improved sensitivity for complications from 98% to 100% and specificity from 0% to 74%. The number of blood tests requested reduced by 73% ( P  < 0.001). Discharge delays reduced from 6% to 0% ( P  = 0.008). Cost savings were £178 per patient. Conclusion: Postoperative complications and transfusion following RARP are rare. Routine POBT without clinical indication are unnecessary and inefficient. A guideline-based approach to POBT can reduce costs and optimise discharge without compromising patient safety or care. Take-home Message: Routine postoperative blood tests following robot assisted radical prostatectomy are often unnecessary. A guideline-based approach can reduce costs and optimise patient care.